IMF Staff papers : Volume 18 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1971)
This paper focuses on the IMF's credit policy and the balance of payments. The attempts at simplicity in the construction of the IMF's models have necessarily involved recognizing the fact that models for different types of countries had to bring out different main features. In models for developing countries it was reasonable to assume that there was little organized capital market, that credit was rationed, that holdings of money were predominantly transactions balances and insensitive to interest rates, that capital flows were largely autonomous, and that the money supply tended to respond to the overseas balance. The simplification involved in the model fails to reflect some important features of economies with highly developed financial markets. The model, although it contains the major behavioral features to be found in macro models of the industrial countries, nevertheless lacks several refinements. The long-run effects on income of increases in exports or net capital inflows are identical in the two models, where imports must rise in equilibrium to match the increase in foreign receipts.